Improved photoluminescence from electrochemically passivated GaSb - Salesse, A; Alabedra, R; Chen, Y; Lakrimi, M; Nicholas, R; Mason, N; Walker, P (1997)
A new class of insulating and passivating layers on gallium antimonide has been prepared by means of an electrochemical process. In previous work we used this new process of fabrication of passivating and insulating layers for gating devices made from GaSb/InAs/GaSb nanostructures (Chen Y et al 1994 Superlatt. Microstruct. 15 41 and Chen Y 1995 PhD Thesis Hertford College, Oxford, UK). In this publication we describe the effects of the electrochemical process leading to an improvement of the photoluminescence (PL) after the growth of the passivating layer on GaSb. The PL measurements on <100>, <111A> and <111B> GaSb substrates and on GaSb epilayers grown by MOVPE on GaAs indicate significant improvement of the PL intensity even after 12 months. Similar results have been observed on InGaSb/GaSb superlattice structures.